2021
DOI: 10.3390/ijerph18189518
|View full text |Cite
|
Sign up to set email alerts
|

Immediate Effects of Acupuncture on Explosive Force Production and Stiffness in Male Knee Joint

Abstract: Acupuncture can improve explosive force production and affect joint stiffness by affecting muscle activation levels. This study aims to explore the effects of true acupuncture (TA) compared with sham acupuncture (SA) on the explosive force production and stiffness of the knee joint in healthy male subjects. Twenty subjects were randomly divided into the TA group (n = 10) and SA group (n = 10) to complete isokinetic movement of the right knee joint at a speed of 240°/s before and after acupuncture. Futu (ST32),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 49 publications
0
8
0
Order By: Relevance
“…Although its exact mechanisms are still being studied and debated, acupuncture has been used to treat a wide range of conditions, including chronic pain, stress, anxiety, insomnia, nausea, and other ailments. In addition to being used by many athletes, this methodology has recently been the subject of several research studies, which have evaluated its effectiveness in positively influencing PAP on shoulder muscles [111][112][113] . In the study by Wang et al 111 , twenty healthy female volunteers were given a 15-minute acupuncture protocol in the area around the shoulder before and after a battery of strength tests.…”
Section: Accommodating Resistance Trainingmentioning
confidence: 99%
“…Although its exact mechanisms are still being studied and debated, acupuncture has been used to treat a wide range of conditions, including chronic pain, stress, anxiety, insomnia, nausea, and other ailments. In addition to being used by many athletes, this methodology has recently been the subject of several research studies, which have evaluated its effectiveness in positively influencing PAP on shoulder muscles [111][112][113] . In the study by Wang et al 111 , twenty healthy female volunteers were given a 15-minute acupuncture protocol in the area around the shoulder before and after a battery of strength tests.…”
Section: Accommodating Resistance Trainingmentioning
confidence: 99%
“…A few recent randomized controlled trials (RCTs) showed acupuncture to be superior to sham acupuncture in terms of muscular force production, with two studies using a noninsertional sham and one study using superficial needling as sham. An RCT by Wang et al (44) investigated the effect of true versus sham acupuncture on force production and stiffness of the knee in 20 healthy men. The subjects were divided into a true and sham acupuncture group, and five traditional acupuncture points on the thighs and lower legs were treated in both groups.…”
Section: Strength and Powermentioning
confidence: 99%
“…Flexibility refers to the ability of muscles to allow joints to move through their full ROM (41). Needling (both acupuncture and dry needling) is thought to improve muscle strength and power through changes to spinal or cortical motor neuron excitability (42), activation of peripheral muscle receptors to improve motor unit recruitment (43), facilitation of postactivation potentiation which increases the capacity of the myosin light-chain kinase and sensitivity of actin and myosin to Ca 2+ (43,44), and increasing coordination between muscles to improve maximum power (44). Needling also deactivates trigger points, which have been associated with muscle stiffness, pain, fatigue (45), and decreased strength (46).…”
Section: Needling For Sports Performancementioning
confidence: 99%
“…With regards to the activation of the primary motor cortex, it is suggested that a strong deqi sensation is required. Sun, et al [25] Wang, et al [26] and Yang, et al [27] established that acupuncture at ST-36 acupoint produces a strong deqi sensation that activated different nerve fibers which affect the excitability of the motor cortex and was correlated to Motor-Evoked Potential (MEP). Although there is convincing evidence to support the requirement of a strong deqi sensation at classical acupoints to affect the motor cortex and produced a strong MEP, amplitude studies investigating osteoarthritis have reached conflicting conclusions.…”
Section: The Effect Of Deqi Sensation On the Motor Cortexmentioning
confidence: 99%
“…The effect of PAP and PAPE is greater in type II fast-twitch fibers [52] than in type I slow-twitch fibers [53] as type II fibers have a lower basal Ca 2+ sensitivity [54,55]. In 2021 Wang and colleagues [26] undertook two studies, one to investigate the immediate effect of acupuncture on the explosive force of the knee joint and the other to investigate the effect of acupuncture on the timeline of male shoulder joint endurance. Both studies demonstrated that selecting and stimulating acupoints around the shoulder joint (LI-14, SJ-14, SJ-13, LU-1, LU-4, LU-3 and SJ-12) or the knee joint (ST-32, ST-34, ST-36, SP-10 and UB-57) activate the nerves and muscles around these joints.…”
Section: Local Response Of Acupuncture In the Production Of Acute Mus...mentioning
confidence: 99%